Spremembe ustavne ureditve Državnega sveta - Štrus, Dušan (Pravnik, 2023)
The National Council, Slovenia’s second parliamentary chamber, was created as a compromise of different ideas during the formation of the Slovenian Constitution. This article traces the evolution of the idea of a bicameral parliamentary system from the late 1980s of the 20th century to the beginning of the 1990s when this idea was embedded in the current Constitution through the draft and proposal of the Constitution. The compromise reached during the drafting of the Constitution affected the law regulatory arrangement of the National Council, leading to numerous practical challenges. The aim of this article is to explore the spectrum of potential amendments to the constitutional regulation of the National Council in several directions, spanning from abolition to transformation and modification of the existing regulation of the National Council. In the remaining part of the article, a change to the regulation of the procedure for reconsidering the law is presented with the aim to bolster the quality of the adopted legislation. As a solution, it is proposed that, instead of voting on the law again, which represents a pointless prolongation of the legislative procedure, the arrangement de lege ferenda enables a discussion of the disputed provisions of the law and a decision on possible changes to the disputed part of the law, thereby obviating unnecessary further procedures for amending the law.
Keywords: Državni svet; parlamentarno pravo; ustavna ureditev; zakoni